Spectrophotometric studies using ion-pair formations of Ranitidine hydrochloride in pure and in Pharmaceutical forms with some dyestuff reagents - M. M. Khalila, E. Y. Z. Fragb, Gehad G. Mohamed & b and Gamal M. Abed el Aziza (Journal of Applied Pharmaceutical Science, 2013)
Simple, rapid and sensitive spectrophotometric procedure is suggested for the determination of ranitidine hydrochloride (RNH) drug in pure form and in pharmaceutical formulations. The method was based on the ion-pair formations of RNH with different dyestuff reagents such as methyl orange (MO), bromocrysol purple (BCP), eriochrome cyanine R (ECR) and alizaraine red S (ARS). The obtained ion-pairs were measured spectrophotometrically at 408, 420, 330 and 326 nm by using BCP, MO, ECR and ARS reagents, respectively. Beer’s plots were linear in the concentration range of 5-200, 20-350, 10-150 and 10-180 µg mL−1 RNH, with correlation coefficients not less than 0.9991, 0.9996, 0.9993 and 0.999 using BCP, MO, ECR and ARS reagents, respectively. The Sandell sensitivity was found to be 0.813, 0.462, 0.541and 0.630 µg cm−2 for BCP, MO, ECR and ARS, respectively. Standard deviation (SD = 0.024-0.028, 0.018-0.023, 0.016-0.021 and 0.023–0.029) and relative standard deviation (RSD% = 0.123-0.943, 0.0102-0.82, 0.118-0.145 and 0.132-0.178%) (n = 4) values using BCP, MO, ECR and ARS reagents, respectively, were obtained. These results were also confirmed with percent recovery of 99.78–100.52%, 99.86-101.12%, 99.82–100.31% and 100.18-101.25 % for BCP, MO, ECR and ARS reagents, respectively. This method was successfully applied for determination of RNH in aciloc tablet. The calculated t- and F- values (95% confidence limit) indicate no significant differences between the proposed and official methods.
Keywords: Ranitidine hydrochloride, BCP, MO, ECR, ARS, ion pai